Clinical Analysis of Four Patients with Schimke Immuno-Osseous Dysplasia and a Literature Review - HAN Lingli; DONG Yajuan; SUN Bijun; WANG Wenjie; ZHOU Qinhua; LIU Luyao; HOU Jia; WANG Xiaochuan; SUN Jinqiao (罕见病研究)
ObjectiveTo have better clinical understanding of Schimke immuno-osseous dysplasia(SIOD) through analyzing the clinical features, treatment, and prognosis of four patients with SIOD.MethodsWe used retrospective analysis to analyze the clinical data of four patients who were diagnosed with SIOD at the Children′ hospital of Fudan University from May 2018 to June 2024.ResultsThe onset of disease of the four patients of this study was in their early childhood or preschool. All four patients had lymphopenia. Two patients had proteinuria, and one patient has progressed to chronic renal failure. One patient presented with short stature. The treatment for the four patients was mainly by symptomatic supportive therapy and on prevention and delay of renal failure disease.ConclusionsThe patients with SIOD have different onset symptoms and progression of the disease.The treatment has not yet completely cured the disease. The clinical diagnosis and treatment of SIOD remains a challenge and needs further investigating.